2011
DOI: 10.1186/1475-2875-10-295
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anti-plasmodial activity of Dicoma anomala subsp. gerrardii (Asteraceae): identification of its main active constituent, structure-activity relationship studies and gene expression profiling

Abstract: BackgroundAnti-malarial drug resistance threatens to undermine efforts to eliminate this deadly disease. The resulting omnipresent requirement for drugs with novel modes of action prompted a national consortium initiative to discover new anti-plasmodial agents from South African medicinal plants. One of the plants selected for investigation was Dicoma anomala subsp. gerrardii, based on its ethnomedicinal profile.MethodsStandard phytochemical analysis techniques, including solvent-solvent extraction, thin-layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…The majority of the plants used by the Basotho for the treatment of venereal sores are used for herpes (15), these include Agave americana, A. ferox, Buddleja salviifolia, Elephantorrhiza elephantina, L. sericea, M. parviflora, Olea europaea ssp. africana, and Searsia lancea, with only three used for syphilic sores, namely A. hispida, Monsonia brevirostrata, and Wahlenbergia banksiana, and one (Scabiosa columbaria), for the treatment of venereal (unspecified) sores.…”
Section: Plants Used For Venereal Sores/ulcersmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the plants used by the Basotho for the treatment of venereal sores are used for herpes (15), these include Agave americana, A. ferox, Buddleja salviifolia, Elephantorrhiza elephantina, L. sericea, M. parviflora, Olea europaea ssp. africana, and Searsia lancea, with only three used for syphilic sores, namely A. hispida, Monsonia brevirostrata, and Wahlenbergia banksiana, and one (Scabiosa columbaria), for the treatment of venereal (unspecified) sores.…”
Section: Plants Used For Venereal Sores/ulcersmentioning
confidence: 99%
“…Datura stramonium, Gunnera perpensa, R. prinoides, Salix mucronata, S. nigrum, and Withania somnifera for their chemical properties. Presence of a wide array of chemical compounds has been reported in several plants (number shown in brackets) including alkaloids (15), anthraquinones (8), coumarins (2), flavonoids (19), glycosides (17), saponins (15), tannins (14), and terpenoids (11). Many of these compounds are known to have several pharmacological effects such as anti-allergic, antibacterial, antifungal, anti-inflammatory, anti-mutagenic, antiplasmodial, antioxidant, and anti-tumour, to name but a few.…”
Section: Phytochemical Datamentioning
confidence: 99%
“…Two subspecies of D. anomala occur in South Africa: D. anomala sub sp anomala and D. anomala subsp. gerrardii (Becker et al, 2011). Phytochemical investigations of D. anomala have identified several classes of secondary metabolites; including acetylenic compounds, phenolic acids, flavonoids, sesquiterpene lactones, triterpenes and phytosterols (Becker et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…gerrardii (Becker et al, 2011). Phytochemical investigations of D. anomala have identified several classes of secondary metabolites; including acetylenic compounds, phenolic acids, flavonoids, sesquiterpene lactones, triterpenes and phytosterols (Becker et al, 2011). Dicoma anomala is used as a root decoction for blood disorders, colic, diarrhoea, dysentery, toothache, and purgative for intestinal worms (Kazembe & Chinyuku, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The study reported that the extract of plants in Asteraceae family has antimalarial activity against various types of Plasmodium. [3][4][5] In addition, a study in 2015 found that the extract of the family Asteraceae exhibits antioxidant and antibacterial activities. 6,7 The mechanism of action of antibacterial drugs is slightly similar to that of antifungal drugs and antimalarial/antiplasmodium; therefore, it is hypothesized that E. valerianifolia is likely to possess both antifungal and antiplasmodium activities.…”
Section: Introductionmentioning
confidence: 99%